Formation a methodology of integral assessment for regional economic entities’ level of financial stability - Evgenii P. Mitrofanov; Alevtina G. Kulagina; Tatyana V. Antipova; Elena A. Solodova (RUDN Journal of Economics, 2022)
The article is devoted to the analysis of existing domestic and foreign methods for assessing the probability of bankruptcy of organizations in the region. When assessing the financial stability of the entity’s enterprises, various methods are used to assess the financial stability of an organization, the most common approach of which is the coefficient method. However, methods that use factor analysis, which builds a linear dependence of indicators of the financial and economic condition of a regional subject, are gaining popularity. These models are also called bankruptcy prediction models. One of the most popular models is Altman’s five-factor forecasting model and the four-factor model for non-manufacturing organizations. Altman’s approach is simple and versatile. However, this Altman model does not take into account the individuality of the company. British scientists G. Tishaw and R. Taffler modernized Altman’s model. One of the first Russian models for predicting the bankruptcy of economic entities was developed by A.Yu. Davydova and A.Yu. Belikov. This model took into account the relationship between such factors as working and equity capital, assets, net profit, cost and revenue. The following model, showing the financial stability of an enterprise, was formulated by Savitskaya. From the analysis of existing methods and models for assessing the financial and economic condition of regional economic entities, it follows that it is advisable to build a model taking into account: firstly, the individual characteristics of a particular organization; secondly, the choice of indicators and their weighting coefficients in the model must be scientifically justified. Therefore, the paper proposes to determine the financial stability of an organization in the region to form a model that includes the most commonly used in practice, namely the above five models for assessing the probability of bankruptcy of enterprises. At the same time, the industry specifics of organizations were taken into account. The purpose of the study is to form a methodology for assessing the integral level of financial stability of organizations in the region and determining the possible boundaries of its variation. In the course of the study, such methods as comparative, component and factor analysis, experiment were used. The paper presents a methodology for the formation of a generalized factor model for assessing the level of financial condition of regional organizations. The critical values of the integral indicator characterizing the level of financial condition of organizations are also determined.